CONTINUOUS INTEGRATION AND DELIVERY OF WEB APPLICATIONS - Brituškins, Aleksandrs; Zorins, Aleksejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
With the advent of DevOps practice, rapidly began evolve systems development life cycle shorting methods, such as continuous integration, testing and delivery, release automation and infrastructure as code methods. This methods, is similar to programming scripts which are used to automate a series of static steps to complete defined scenario. Often, the choice of used automation methods and tools depends on project and application complexity, which makes each case unique in its own way. The main goals of the paper are description of basic continuous integration and delivery methods for web based applications with real example using version control system, container virtualization and some auxiliary scripts, which developed by author and currently being successfully used on few real projects. In example used version control system, container virtualization and some auxiliary scripts.